2005
DOI: 10.1167/5.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of saccade and vergence eye movements in 3D space

Abstract: Inhibitory capacity was investigated by measuring the eye movements of normal subjects asked to fixate a central point, and to suppress eye movements toward visual distracters appearing in the periphery or in depth. Eight right-handed young adults performed such a suppression or distracter task. In different conditions, the distracter could appear at 10 degrees left or right at a distance of 20, 40, or 150 cm (calling for horizontal saccades), or in a central position far or close (calling for convergence or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 91 publications
8
70
1
2
Order By: Relevance
“…However, the latter was correlated neither to visually-guided saccades, to express saccades, nor to erratic saccades in the antisaccade task [24]. In a recent study using a distracter task, we also observed a rightward bias in microsaccadic activity, particularly at close distance [12]. This set of results suggests that we do not explore visual left and right spaces similarly.…”
Section: Characteristics Of Saccades During Symmetrical Vergencecontrasting
confidence: 62%
See 1 more Smart Citation
“…However, the latter was correlated neither to visually-guided saccades, to express saccades, nor to erratic saccades in the antisaccade task [24]. In a recent study using a distracter task, we also observed a rightward bias in microsaccadic activity, particularly at close distance [12]. This set of results suggests that we do not explore visual left and right spaces similarly.…”
Section: Characteristics Of Saccades During Symmetrical Vergencecontrasting
confidence: 62%
“…Monophasic square wave intrusions (MSWI), biphasic square wave intrusions (BSWI), single saccadic pulses (SSP) and double saccadic pulses (DSP) have been previously described by Abadi and Gowen during fixation [1]. For MSWI, we used an upper limit of 500 ms as inter-saccadic delay [12]. Among SSP occurring during vergence, we distinguished between SSP followed by a backward drift (SSPbd) and SSP followed by an ownward drift (SSPod).…”
Section: Horizontal Saccadic Component Morphologymentioning
confidence: 99%
“…In all, we suggest that the short-latency triggering described to date for saccades can generalize symmetrical convergence (without the contribution of saccades) under particular conditions of spatial arrangement and prefrontal disinhibition. This assumption is supported by a recent study showing that unwanted short-latency convergence could occur when a convergence distracter has to be ignored (Coubard and Kapoula, 2005).…”
Section: Discussionmentioning
confidence: 76%
“…Anticipated divergence contrasted convergence that was little anticipated and could be explained by some passive relaxation of the eyes. Against this hypothesis is our recent observation in a distracter task: when normal subjects were asked to fixate a position on the median plane and ignore distracters presented in depth (either in front of or behind the fixation location), they almost never diverged spontaneously but, in contrast, were prone to produce convergence erratic movements or a convergent drift (Coubard and Kapoula, 2005). Thus, the anticipatory mode of triggering for divergence, also described in prior studies (Takagi et al, 1995;Coubard et al, 2004), would rather be a volitional behavior that may correspond to a phylogenetic survival of an oculomotor function aiming to rapidly detect a predator or a prey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation